Enacting the curriculum: The interplay of pedagogical beliefs, motivation, and fidelity - Özgür Tutal (PLoS ONE, 2026)
Background Curriculum fidelity – the balance between strict adherence to prescribed curricula and context-responsive adaptation – represents a critical challenge in educational implementation, particularly within centralized systems. While curriculum design has evolved toward constructivist, student-centered approaches, teachers must navigate tensions between mandated standards and diverse classroom realities. This study examines how teachers’ pedagogical beliefs (constructivist versus traditional) and teaching motivation (intrinsic versus extrinsic) interact to shape curriculum enactment decisions. Methods A quantitative correlational design was employed with 424 in-service teachers from southeastern Türkiye. Participants completed validated scales measuring pedagogical beliefs, teaching motivation, and curriculum fidelity, which assessed both adherence and adaptation dimensions. Structural equation modeling with mediation analysis was conducted to test direct and indirect pathways among latent variables. Results Constructivist beliefs were positively associated with curriculum adaptation and intrinsic motivation, while traditional beliefs showed positive associations with adherence and extrinsic motivation. Critically, intrinsic motivation was positively associated with adaptation and negatively associated with adherence. Conversely, extrinsic motivation was positively associated with adherence and negatively associated with adaptation. Mediation analysis indicated that both motivation types partially mediated the belief-fidelity relationships, revealing motivation as an important pathway linking beliefs and enactment preferences. Conclusion The study illuminates the critical role of teachers’ teaching motivation in the relationship between pedagogical beliefs and curriculum implementation. By understanding how teaching motivation acts as a conduit between pedagogical beliefs and curriculum fidelity, educators and policymakers can develop targeted interventions to optimize curriculum effectiveness, fostering environments that support both teacher autonomy and curriculum integrity.